2015
DOI: 10.1111/1753-0407.12263
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of B lymphocyte responses to Toll‐like receptor ligand binding during diabetes prevention in non‐obese diabetic (NOD) mice

Abstract: Background Interactions between genetic risk factors and the environment drive Type 1 diabetes. The system of Toll-like receptors (TLR) detects these environmental triggers; however, the target cell that intermediates these interactions to drive T1D remains unknown. Methods We investigated the effect of TLR pathway activation (MyD88 vs TRIF) on B cell subsets via flow cytometry including their activation, survival, proliferation and cytoskeletal mobilization. The effect of polyIC on diabetes development was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Unlike all other TLRs, TLR3 is MYD88-independent and instead utilizes the adaptor molecule TRIF for signal transduction following activation ( 44 ). The dsRNA mimetic polyinosinic:polycytidylic (poly I:C) is recognized by TLR3 and has been shown in various mouse studies to either protect or induce and increase severity of T1D depending on dose and administration ( 48 50 ). NOD mice deficient for TLR3 have high mortality from CVB4 infections and the few that survive develop T1D ( 51 ).…”
Section: Tlrs In T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike all other TLRs, TLR3 is MYD88-independent and instead utilizes the adaptor molecule TRIF for signal transduction following activation ( 44 ). The dsRNA mimetic polyinosinic:polycytidylic (poly I:C) is recognized by TLR3 and has been shown in various mouse studies to either protect or induce and increase severity of T1D depending on dose and administration ( 48 50 ). NOD mice deficient for TLR3 have high mortality from CVB4 infections and the few that survive develop T1D ( 51 ).…”
Section: Tlrs In T1dmentioning
confidence: 99%
“…However, in some instances, TLR3-KO NOD mice can show less severe insulitis as well as some reduced susceptibility to T1D induction following CVB4 infection, but experience no difference in spontaneous disease development ( 52 ). TLR3 signaling within resident macrophages is critical for antiviral host defense to CVB4 as well as altering marginal zone B cell composition in NOD mice ( 50 , 51 ). This indicates that enhanced TLR3 activation may participate in T1D development as a result of virus infection.…”
Section: Tlrs In T1dmentioning
confidence: 99%
“…For analysis of healthy aged mice (29 months-old), the mice were starved for 5 hours and crown-to-rump length was measured. Blood was collected and analyzed for blood glucose levels with Accu-chek test strips (Roche Diagnostics, Indianapolis, IN, USA; [41], centrifuged and plasma frozen for later analysis. Mice were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, BTK mutation in the particular patient does not lead to complete loss of Β -cells [ 55 , 56 ]. In addition, active B-cells from NOD mice express increased levels of TLR-responsive proteins, which mediate TLR3-induced diabetes protection [ 57 ]. Furthermore, clinical trials have identified B-cells as possible therapeutic target for the prevention and reversal of T1DM [ 58 ].…”
Section: Adaptive Immunity In T1dmmentioning
confidence: 99%